First mail west: Stagecoach lines on the Santa Fe Trail - Taylor, Morris F. frey50 (University of New Mexico Press Albuquerque, NM, 1971)
Morris Taylor tells the story of the stagecoach lines that carried passengers and mail over the Santa Fe Trail from 1850 - 1879, when the railroads took over their traffic. It is a history of the transportation business that helped build the Southwest, the roads used, the stations and passenger accomodations, the nature of the country, the people, and the trade at the end of the route in New Mexico.
Keywords: Transportation - Stagecoaches - History -- Santa Fe Trail - Transportation - History -- Stagecoach lines - Transportation - History